The Malaysian Corporate Governance Reform and Financial Reporting Quality - Nahar, Hairul Suhaimi (2010)
Chains of critical corporate and economic events pre and post millennium periods have dramatically shifted the focus of firms, investors and regulators worldwide on corporate governance and financial reporting issues. Particularly, the 1997/1998 Asian financial crisis has motivated many Asian countries including Malaysia to reform their respective governance regime. This study undertakes an empirical investigation with regards to the Malaysian public policy reform effectiveness related to corporate governance from the specific perspective of firm’s financial reporting quality (FRQ). The motivation behind this study is the propositions set out by the Malaysian government upon introducing series of governance reform programs which includes the expectation that reform programs would improve directors’ monitoring and oversight effectiveness towards financial reporting matters. These propositions are considered in this study as “maintained assumptions”, which become the subject of the empirical investigation. Accordingly, three research objectives and three main hypotheses were established. Six board characteristics and two ownership types were selected, representing the predictor variables. Contributing to the body of governance knowledge is the consideration given to a new director’s characteristic of social title which is Malaysia’s unique board feature. Other board characteristics include leadership structure, independence, multiple directorships, founding family directors and financial expertise. The two considered ownership types are directors’ and institutions’ and the FRQ being the dependent variable is proxied by accruals quality metrics commonly used in prior FRQ studies. A total of one hundred and three survived listed firms in Bursa Malaysia throughout the eleven years period from 1996 to 2006, with complete data were chosen. The survived firms were sampled to accommodate the balanced observations research design, thereby facilitating the objective assessment of governance reform implications on firm’s FRQ. The regression analyses were done separately to reflect the two separate reform types of regulatory (reform-I) and institutional and best practices (reform-II). This thesis postulates that the introduction of both reform types would introduce an inflexion point to firm’s FRQ (i.e. improvement) and favorably moderate the statistical relationships between firm’s FRQ and both, board and ownership variables. The results indicate that majority (88% in reform-I and 75% in reform-II analysis period) of the predictor variables considered in this study are significant determinants of FRQ (in the predicted direction) in Malaysia. The interaction results (testing on reforms’ moderating effect) generally reflect poor ability of reform-I to favorably moderate the link between predictor variables and FRQ as compared to reform-II, indirectly suggesting higher moderating effectiveness of reform-II. The study is however unable to find any evidence of FRQ improvement post reform periods. Three reasons of (1) the macroeconomic condition; (2) the importance of governance in enhancing firm’s FRQ; and (3) the presence of unique, country-specific economic and governance characteristics are suggested to explain the findings. The sensitivity tests results suggest that, except for some minor differences in results, these findings are moderately robust to alternative variables specification and study period. Overall, this study contributes to the extant of governance literature in emerging economies by evidencing that governance reform effectiveness in ensuring firm’s FRQ is sensitive to economic conditions and various unique governance and institutional characteristics.